2007
DOI: 10.1051/0004-6361:20078332
|View full text |Cite
|
Sign up to set email alerts
|

The great observatories origins deep survey

Abstract: Aims. We present the full data set of the spectroscopic campaign of the ESO/GOODS program in the GOODS-South field, obtained with the FORS2 spectrograph at the ESO/VLT. Methods. Objects were selected as candidates for VLT/FORS2 observations primarily based on the expectation that the detection and measurement of their spectral features would benefit from the high throughput and spectral resolution of FORS2. The reliability of the redshift estimates is assessed using the redshift-magnitude and color-redshift di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
372
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 335 publications
(384 citation statements)
references
References 42 publications
8
372
1
3
Order By: Relevance
“…[44]). The spectra have been obtained from VVDS [45], VIMOS [46], and FORS2 [43,47]. Mass estimates have been taken from Ref.…”
Section: Goods-s Samplementioning
confidence: 99%
See 1 more Smart Citation
“…[44]). The spectra have been obtained from VVDS [45], VIMOS [46], and FORS2 [43,47]. Mass estimates have been taken from Ref.…”
Section: Goods-s Samplementioning
confidence: 99%
“…Old passive ETGs were extracted from the GOODS-S field [43] combining morphological and photometric criteria based on optical color cuts as a function of redshift (for more details on the sample selection, see Ref. [44]).…”
Section: Goods-s Samplementioning
confidence: 99%
“…When a spectroscopic redshift is present, the relative source catalog is reported, as follows: (1) CXO-CDFS (S04); (2) K20 (Mignoli et al 2005); (3) GOODS (Vanzella et al 2005(Vanzella et al , 2006(Vanzella et al , 2008Popesso et al 2008); (4) COMBO-17 (Wolf et al 2003); (5) VVDS (Le Fevre et al 2004); (6) other Cristiani et al 2000). Otherwise, the redshift is from SED fitting ) and is reported with its 1σ confidence interval.…”
Section: Optical+infrared Photometry and Photometric Redshiftsmentioning
confidence: 99%
“…Photometric redshifts were estimated using GAaP magnitudes with BPZ, following Hildebrandt et al (2012). Kuijken et al (2015) compared the photometric redshifts to ∼17 000 spectroscopic redshifts in the zCOSMOS (Lilly et al 2007) and ESO/GOODS (Vanzella et al 2008;Balestra et al 2010) surveys. They found that the peak of the posterior distribution, z B , is biased by less than 2 per cent in the range 0.005 < z B < 1.0.…”
Section: Photometric Redshiftsmentioning
confidence: 99%